2016
DOI: 10.1002/pssb.201600457
|View full text |Cite
|
Sign up to set email alerts
|

Intense laser field-induced nonlinear optical properties of Morse quantum well

Abstract: Abstractauthoren This paper investigates the effects of an intense laser field and electric field on the optical properties of quantum well represented by Morse potential. The non‐resonant, high‐frequency intense laser effects upon the system are treated within the framework of non‐perturbative approach, modifying the confinement potential associated to the heterostructure. The analytical expressions of the linear and third‐order nonlinear optical absorption coefficients and refractive index changes are obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 42 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…We have to remark that despite the system under debate is the same as in Ref. [31], the optical characteristics investigated in both papers are different.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have to remark that despite the system under debate is the same as in Ref. [31], the optical characteristics investigated in both papers are different.…”
Section: Introductionmentioning
confidence: 93%
“…Very recently, Ref. [31] analyzed the combined effects of electric field and high-frequency intense laser field on the linear and third-order nonlinear optical absorption coefficients and refractive index changes.…”
Section: Introductionmentioning
confidence: 99%
“…We have to stress that the agreement between the results obtained via the two methods was perfect. Then, the first-order linear, third-order nonlinear, and total absorption coefficients (ACs) for the transitions between the ground and first excited states of electron confined within DMQW by following the standard density matrix formalism combined with the perturbation expansion method are obtained, respectively, as follows [9], [19], [20], [21], [31], [32], [33], [34]βfalse(1false)false(Epfalse)badbreakafter=Epħ0.2emμ0εR0.2emfalse|M12false|20.2emσv0.2emnormalΩ12false(E12badbreakafter−Epfalse)2badbreakafter+normalΩ1220.2em,βfalse(3false)false(Ep,Ifalse)badbreakafter=badbreakafter−0.2em20.2emI0.2emβfalse(1false)false(Epfalse)ε00.2emn…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These models provide a useful approximation for the potential energy of a diatomic molecule. Nonlinear optical properties of semiconductor QWs mainly depend on the asymmetry of the confinement potential and so the optical properties of the low dimensional semiconductor heterostructures with the Morse potential, due to the inherent asymmetric character, have been studied intensively [19], [20], [21], [22]. However, as far as we know, any study has not been reported on the optical properties of double Morse potential quantum wells in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Podemos mencionar, por ejemplo, la presencia de cambios en la densidad electrónica de estados en pozos cuánticos (QWs), la medición de estados de resistencia cero en gases de electrones bidimensionales bajo radiación de microondas, absorción resonante de terahertz en QWs, y estados de Floquet-Bloch en nanotubos de carbono de pared simple, entre otros. Por lo tanto, estas perturbaciones externas pueden considerarse como una herramienta poderosa para el control de las propiedades electrónicas y ópticas de las nanoestructuras semiconductoras (Sakiroglu, 2017). Los campos electromagnéticos ILF y externos proporcionan un efecto importante en las propiedades electrónicas y ópticas de pozos cuánticos dobles asimétricos (ADQWs), y los cambios en los niveles de energía y los elementos de la matriz del momento dipolar dependen de la forma del potencial de confinamiento (Yesilgul, 2017).…”
Section: Introduciónunclassified